Cardiovascular disease mortality in patients with genetically verified familial hypercholesterolemia in Norway during 1992–2013. (29th August 2020) - Mundal, Liv; Igland, Jannicke; Ose, Leiv; Holven, Kirsten B; Veierød, Marit B; Leren, Trond P; Retterstøl, Kjetil
Abstract: Background: Patients with familial hypercholesterolemia have increased cardiovascular disease mortality but the magnitude of the increased risk is uncertain. The primary aim of this study was to investigate all causes of death and place and manner of deaths in a large sample of genotyped familial hypercholesterolemia patients. Design, methods and results: In this registry study data on 5518 patients with genotyped familial hypercholesterolemia were linked to the Norwegian Cause of Death Registry during 1992–2013. Standardized mortality ratios and 95% confidence intervals (CIs) were estimated. There were in total 189 deaths. Cardiovascular disease was the most common cause of death (42.3%). Mean age at cardiovascular disease death was 64.5 years (range 33–91). Cardiovascular disease mortality including all cardiovascular disease deaths mentioning any place on the death certificate was significantly higher in familial hypercholesterolemia patients compared to the general Norwegian population under 70 years of age. Standardized mortality ratio (95% CI) was highest in the 20–39 years age group; 4.12 (1.85–9.18) decreasing to 0.77 (0.50–1.19) for those over 80 years. For total cardiovascular disease deaths occurring out of hospital, standardized mortality ratio was 12.35 (5.14–29.70) for those aged 20–39 years. Conclusion: Familial hypercholesterolemia patients under 70 years of age have significantly higher cardiovascular disease mortality compared to the general Norwegian population. For those aged 20–39 years the risk of cardiovascular disease deaths occurring out of hospital was increased 12-fold. In spite of genotyped familial hypercholesterolemia and premature cardiovascular disease deaths, the majority of all death certificates did not include familial hypercholesterolemia among any of the contributing causes of death.